Long‐Term Outcome of Additional Superior Vena Cava to Septal Linear Ablation in Catheter Ablation of Atrial Fibrillation - Moo‐Nyun Jin; Byounghyun Lim; Hee Tae Yu; Tae‐Hoon Kim; Jae‐Sun Uhm; Boyoung Joung; Moon‐Hyoung Lee; Chun Hwang; Hui‐Nam Pak (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background We previously reported the benefit of linear ablation from the superior vena cava to the right atrial septum (SVC‐L) within a year after circumferential pulmonary vein isolation (CPVI) in patients with paroxysmal atrial fibrillation (AF). We explored the long‐term effects of SVC‐L and its potential related mechanisms. Methods and Results Among 2140 consecutive patients with AF ablation, we included 614 patients (73.3% male, aged 57.8±10.7 years, 13.7% with persistent AF) who did not undergo an extra–pulmonary vein left atrial ablation after propensity score matching; of those, 307 had additional SVC‐L and 307 had CPVI alone. We evaluated the heart rate variability and computational modeling study to explore mechanisms. Although the procedure time was longer in the SVC‐L group than the CPVI group (P<0.001), the complication rates did not differ (P=0.560). During 40.5±24.4 months of follow‐up, the rhythm outcome was significantly better in the SVC‐L group than the CPVI group (log rank, P<0.001). At 2‐year follow‐up of heart rate variability, a significantly higher mean heart rate (P=0.018) and a lower ratio of low/high‐frequency components (P=0.011) were found with SVC‐L than CPVI alone. In realistic in silico biatrial modeling, which reflected the electroanatomies of 10 patients, SVC‐L significantly reduced biatrial dominant frequency compared with CPVI alone (P<0.001) and increased AF termination and defragmentation rates (P=0.033). Conclusions SVC‐L ablation in addition to CPVI significantly improved the long‐term rhythm outcome over 2 years after AF catheter ablation by mechanisms involving autonomic modulation and AF organization.